Mengurangi Stigma Sosial : Optimalisasi Peran Bapas dalam Reintegrasi Sosial Melalui Program “Bapas Goes to Village” - Rafi Hafidz; Elin Cantika Sari Saragih; Muhammad Ali Equatora; Umar Anwar (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
This study aims to analyze the role of the Correctional Center (Bapas) in community empowerment through the “Bapas Goes to Village” program and its impact on efforts to minimize social stigma against correctional clients who are carrying out the social reintegration process. The program is designed to increase community understanding of the duties and functions of Bapas and the importance of community involvement in the supervision and guidance of correctional clients. In this study, a qualitative approach was used with a case study method involving in-depth interviews with Bapas officers, correctional clients, and the community around the program implementation location. The results showed that the “Bapas Goes to Village” program plays a significant role in strengthening the synergy between Bapas, correctional clients, and the community. The program succeeded in reducing social stigma by increasing community knowledge and awareness about the importance of social support for correctional clients. Support from various elements of the community proved effective in helping correctional clients adapt back into their social environment, as well as reducing the risk of recidivism.